Systematic review on the Burnout syndrome’s prevalence in the academic sector - Choy Vessoni, Rosana Aurora (2021)
The burnout syndrome has negative consequences over employees in different areas. However, little is stated regarding its specific prevalence in the academic area. The present study seeks to define the prevalence of burnout in teachers and students as presented in the literature. A systematic review is conducted to research the prevalence of the burnout syndrome and its dimensions on the education sector, regarding both teachers and students. 1547 unique references were found, within which 59 reported information on the prevalence of the burnout syndrome in the population of interest. The proportion of high levels of each dimension showed to be higher in students than in teachers. However, the prevalence of the syndrome itself showed opposite results, being more frequent in teachers (Median = 19.8%) than in students (Median = 14.4%). Burnout research is affected by some limitations; particularly, regarding the use of psychometric instruments and cut-off points. Nevertheless, its high prevalence on both teachers and students are enough evidence to further research into its consequences in this specific sector.